URBAN POLITICS IN SURABAYA (The Role of Majelis Ulama Indonesia in East Java to supporting Revitalization Kampong Dolly) - ANDRIYANI, LUSI (Human Sustainability Procedia, 2018)
urban areas are part of the area that has been studied since 1976 along with the debate over urban regime theory in Europe. That is used to view cities as areas that carry out the function of social services and people’s welfare. Surabaya is the second largest city after Jakarta which is indicated in 2015 will be the fifth most populous city in the world. As a mega-urban area, various social problems are emerging as the city develops. One of them is a social problem that comes from urban poverty that prostitution. The issues in this study relate to: How is urban political policy in Surabaya in Tri Rismaharini’s leadership in the case of Dolly Village Revitalization. with using urban regime theory as an analytical tools. The method used in this research is qualitative, which take the object of study in Dolly Village Surabaya. Data taken using interview technique and analyzed in the form of descriptive qualitative. The results obtained in this study illustrates that the Surabaya city government responded to the policy of East Java Provincial Government through the execution closing Prostitution with the Dolly kampongrevitalization program to realize prostitution-free East Java. Many interests play in the Dolly village revitalization program, from academics, bureaucrats, officials, and mass organizations and economic actors. The conclusion obtained in this study is that the government has implemented policies that have the impact of social environment changes in society, especially in the prostitution dolly environment to realize the vision and mission of East Java as a city free of prostitution. Although prostitution is indeed difficult to eradicate, it shows that efforts to compare the city in accordance with its vision and mission have been pursued by various conflicts and conflicts therein